363 Using the socio-ecologic model as a guide for agricultural safety interventions. (1st September 2016) - Lee, Barbara C; Salzwedel, Marsha; Weichelt, Bryan; Bendixsen, Casper
Abstract : Background: Agriculture is a dangerous industry that allows children in the worksite. Each day about 38 children are seriously injured on farms. The culture of agriculture resists advice from outsiders. Farm operators/parents prefer receiving information from familiar sources, not safety professionals. The Socio-ecologic Model (SEM) demonstrates how spheres of increasing influence have higher degrees of impact on individual behaviour. Methods: We modified the SEM to have farm children as the focal point, with adults/parents the first line of protection. Increasing spheres of influence are family and friends, followed by the community, organisations, and businesses. Public policy has the greatest influence but in agriculture rarely applies. Key farm business contacts are property and liability insurance providers. We conducted a study to assess if and how insurers could influence farmers regarding childhood farm safety. Surveys were distributed at a farm risk management training with 96 (55%) insurers responding. Results: Agricultural insurers reported 55% currently send general safety information and 38% provide financial support of safety events. Regarding child-specific information, 79% want to increase their focus on children and 63% need guidance for this. Furthermore, 76% believe customers would be pleased if they added a focus on childhood farm safety. Using these results, an illustrated report was sent to 150 agricultural insurance companies. It highlighted safety topics of concern, including ATVs and children operating tractors. Details were offered on insurance providers' strategies, such as co-branding farm safety posters, updating farm policies on young workers, and website links to and evidence-based programs. Conclusions: This new approach may influence farmers to protect children from preventable injuries. The project impact, including numbers and types of actions taken by insurance companies, will be shared at the Safety 2016 World Conference.